IMPLEMENTASI KOMUNIKASI PEMASARAN RUMAH SAKIT AWAL BROS PEKANBARU DALAM MEMPERTAHANKAN LOYALITAS KONSUMEN - Anggraeni, Dian Suci; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Marketing communication as communication activities aimed to deliver a message to consumers using a variety of media, with the purpose of communication can generate a positive response from the public. Through marketing communications activities, Awal Bros hospital Pekanbaru can determine the effectiveness of implementation of marketing communications in maintaining customer loyalty. The purpose of this study was to determine the implementation of advertising, face to face sales, sales promotion, direct marketing and public relations in maintaining customer loyalty.This research was conducted at the Awal Bros hospital Pekanbaru. This study uses descriptive qualitative research methods, with the selection of informants using purposive sampling technique, for 7 people informant of business and development divisions were selected based on certain characteristics and 10 people from the consumer by using accidental sampling technique taken by chance. Data collection techniques used is participant observation, in-depth interviews and documentationThe results showed that Awal Bros Hospital maintain consumer loyalty early brooch run marketing communication activities using a mix marketing communications, advertising, personal selling, sales promotion, direct marketing and public relation. The overall implementation of marketing communication does not escape from the media, where the use of the media also plays an important role in the delivery of the message to consumers.Keywords: Marketing Communications, Awal Bros hospital Pekanbaru, consumer loyalty.